SELECTION AND DECISION-MAKING ON MANAGING REPAIRS OF POWER EQUIPMENT IN POWER SUPPLY SYSTEMS WITH MONOCONSUMER - Y. Sekretarev; V. Levin (Вестник Северо-Кавказского федерального университета, 2022)
He article proposes a methodology for selecting and decisions making on the management of repairs of power equipment in industrial power supply systems (IPSS) based on a risk-based approach. An analysis is made of the consequences offailures in the EIT, which lead to damage, both in the power system itself and in its consumers. The case when the IPSS provides power to a mono consumer, which is the case in oil and gas production, is considered separately. Here, the power supply system and the consumer are a single entity. Moreover, the power supply mode is completely subordinate to the technological features of production. Based on the analysis of scenarios for the implementation of the risk-based approach, the influence of varying severity of the consequences of failure in the industrial power supply system on the assessment of decisions was studied. An decision-making algorithm has been developed for prioritizing the conclusion to the repair of power equipment for IPSS.